2012
DOI: 10.2215/cjn.01970211
|View full text |Cite
|
Sign up to set email alerts
|

AKI Associated with Macroscopic Glomerular Hematuria

Abstract: SummaryHematuria is a common finding in various glomerular diseases. This article reviews the clinical data on glomerular hematuria and kidney injury, as well as the pathophysiology of hematuria-associated renal damage. Although glomerular hematuria has been considered a clinical manifestation of glomerular diseases without real consequences on renal function and long-term prognosis, many studies performed have shown a relationship between macroscopic glomerular hematuria and AKI and have suggested that macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
110
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 68 publications
(77 reference statements)
3
110
0
Order By: Relevance
“…[7][8][9] Several pathophysiologic mechanisms may account for the tubular injury found on renal biopsy specimens. 20 However, in our series, MH was only seen in 16 patients in AKI group, and we did not differentiate recurrent MH and isolated MH in this retrospective study. We found that MH was a protective factor for AKI in univariate analysis in our study.…”
Section: Discussionmentioning
confidence: 57%
“…[7][8][9] Several pathophysiologic mechanisms may account for the tubular injury found on renal biopsy specimens. 20 However, in our series, MH was only seen in 16 patients in AKI group, and we did not differentiate recurrent MH and isolated MH in this retrospective study. We found that MH was a protective factor for AKI in univariate analysis in our study.…”
Section: Discussionmentioning
confidence: 57%
“…It is important to note that an episode of MH is also associated with the incidence of acute kidney injury (AKI) [17,20,21,22,23]. The incidence of AKI after episodic MH in IgAN remains unknown; however, once it has occurred, approximately 25-27% of patients do not recover their previous renal function [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AKI after episodic MH in IgAN remains unknown; however, once it has occurred, approximately 25-27% of patients do not recover their previous renal function [20,22]. The most frequent histological findings in MH-associated AKI are acute tubular necrosis and intraluminal obstruction by RBC or hemoglobin casts [17,20,22]. Recent studies suggested that the cytotoxic effects of oxidative stress induced by hemoglobin, heme, or iron released from red blood cells may account for the tubular injury during MH-associated AKI [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preponderance of evidence suggests that unbound heme and free iron are involved in the pathogenesis of tubular injury observed in glomerular hematuria [14,15]. Heme is an integral component of heme proteins such as hemoglobin, myoglobin, mitochondrial cytochromes, and enzymes that regulate vascular tone, redox reactions, cell signaling, DNA transcription, and RNA translation [16].…”
Section: Discussionmentioning
confidence: 99%